The Construction of Cloned Sika Deer Embryos (Cervus nippon hortulorum) by Demecolcine Auxiliary Enucleation. Issue 1 (21st October 2013) - Yin, Y; Mei, M; Zhang, D; Zhang, S; Fan, A; Zhou, H; Li, Z
Contents The objective of our study was to establish the feasibility of experimental protocols for cloning sika deer. We performed auxiliary enucleation to improve the efficiency of nuclear transfer operation by optimizing the demecolcine concentration to induce cytoplasmic protrusions in the sika deer oocytes. In the present study, we had studied the impact of different demecolcine concentrations on cytoplasmic protrusions and enucleation rates. We determined that 95.9% of the sika deer oocytes formed cytoplasmic protrusions when treated for 1 h with 0.8 μg/ml demecolcine. The lowest observed rate of protrusion was 19.3% after overnight treatment with demecolcine. When the oocytes aged or had a poor cumulus expansion, they exhibited a significant decrease in the ability to form cytoplasmic protrusions. The rates of enucleation (94.9% vs 85.8%, p < 0.05), cell fusion (84.6% vs 70.1%, p < 0.05) and blastocyst formation (15.4% vs 10.9%, p < 0.05) using demecolcine auxiliary enucleation were significantly higher than those after blind enucleation. These results demonstrated that sika deer oocytes could be enucleated quickly and effectively using demecolcine auxiliary enucleation, which could enhance the enucleation rate, cell fusion rate and blastocyst rate of cloned embryos in vitro.